Personal experience or cultural tradition: the difference between Christian identity in the Netherlands and Denmark - Storm, Ingrid (Religion, brain & behavior, 2020)
Denmark and the Netherlands are both countries with a Christian heritage, where only a minority of the population are actively religious. Behind the similarities, there are also striking differences. While Danish Christians tend to be largely nominal members, Dutch Christians are more likely to believe in God, pray and attend church regularly. Previous research has highlighted insecurity as a source of national differences in religiosity. In this comparative study, we explore whether insecurity and threat to personal control partially contribute to one or both forms of religiosity, using data from a survey experiment and secondary international survey data. Our main findings are that Danish Christians identify more with Christianity as a cultural tradition, whereas the Dutch Christians identify more with Christianity as personal experience. Christians in both countries were more likely to identify as Christians based on their personal beliefs after a control threat manipulation. This finding suggests that belief in a higher power, rather than group tradition, is the aspect of religious identity that is triggered by insecurity and lack of control.